Fighting the Host Reaction to SARS-COv-2 in Critically Ill Patients: The Possible Contribution of Off-Label Drugs - Scala, Stefania; Pacelli, Roberto (Frontiers in Immunology, 2020)
The severe acute respiratory syndrome corona virus 2 (SARS-COv-2) determines the 2019 corona virus disease (COVID 19). The majority of infected symptomatic people presents flu like symptoms and about 15-20% of patients develops a severe interstitial pneumonitis (IP) that may evolve in acute respiratory distress syndrome (ARDS). IP is caused by the viral glycoprotein (spike, S) binding to the angiotensin converting enzyme 2 (ACE2) expressed on the surface of alveolar pneumocytes. Accumulating evidence suggests that a subgroup of patients with severe COVID-19 might have a cytokine storm syndrome, a fulminant and fatal hypercytokinaemia with multiorgan failure. The virus is recognized by the pattern recognition receptors of immune cells that release cytokines activating more immune cells that produce a large number of pro-inflammatory cytokines, tissue factors and vasoactive peptides. In patients infected by SARS-COv-2 beyond the increase of IL1B, IFNγ, IP10, and MCP1 (macrophage chemo attractant protein 1)/CCL2, probably leading to activated T-helper-1 (Th1) cell responses, also T-helper-2 (Th2) immunosuppressive cytokines, like IL4 and IL10, are increased. Cytokines and the other molecules involved in immune response regulation and inflammation are targets to ameliorate the severity of the lung injury due to IP and ARDS, possibly lowering ICU and/or reducing the recovery time. To this aim, off label drugs may be used, keeping in mind the restricted, well defined timing for immunosuppressive drugs in a virus infected patient. Some off label therapeutic options to manage severe IP and ARDS based on described biological activity are herein considered.